Cancer incidence in British Indians and British whites in Leicester, 2001-2006. - Ali, R; Barnes, I; Kan, S; Beral, V (2010)
BACKGROUND: Incidence rates for many cancers are lower in India than in Britain and it is therefore of interest to compare rates in British Indians to British whites, as well as to rates in India. We present estimates for Leicester, which has the largest population of Indian origin in Britain, and also has virtually complete, self-assigned, ethnicity data. METHODS: We obtained data on all cancer registrations from 2001 to 2006 for Leicester with ethnicity data obtained by linkage to the Hospital Episode Statistics database. Age-standardised incidence rates were calculated for British Indians and British whites as well as incidence rate ratios, adjusted for age and income. RESULTS: Incidence rate ratios for British Indians compared with British whites were significantly less than 1.0 for all cancers combined (0.65) and for cancer of the breast (0.72), prostate (0.76), colon (0.46), lung (0.30), kidney (0.36), stomach (0.54), bladder (0.48) and oesophagus (0.64), but higher than 1.0 for liver cancer (1.95). CONCLUSION: These results are likely to be the most accurate estimate of cancer incidence in British Indians to date and confirm that cancer incidence in British Indians is lower than in British whites in Leicester, particularly for cancer of the breast, prostate, colon and lung (and other smoking-related cancers), but much higher than in India.